Evaluation of virgin coconut oil-in-water emulsion stability: insights from creaming index and polarised light microscopy analyses - Mohammad Latif, Muhammad Alif; Abdul Hamid, Hairul Amani; Rozaini, Muhammad Afif Syazani; Mat Hadzir, Nursyamsyila; Md Som, Ayub (Universiti Putra Malaysia, 2024)
The stability of emulsions containing virgin coconut oil-in-water is crucial for their successful use in food, cosmetics, and medicinal products. The goal was to determine the most stable formulation by examining various ratios of VCO, deionised water, and mixed surfactants (methyl-α-D-glucopyranoside combined with either Span 20 or Span 80). This study examines the stability of these emulsions using two primary analytical techniques: the creaming index quantitatively measures the stability of an emulsion by evaluating the degree of phase separation over a period of time and the optical polarising microscope gives a qualitative evaluation by visualising the microstructure of the emulsion. The creaming index revealed that emulsions prepared with methyl-α-D-glucopyranoside and Span 20 exhibited superior stability compared to those prepared with Span 80. Samples with Span 20 showed low creaming indices, indicating minimal phase separation. Samples L1 and M1, including 15 % w/w of methyl-α-D-glucopyranoside and 15 % w/w of Span 20, were the most stable formulations; they did not phase separate at all throughout the storage time. These results were corroborated by the optical polarising microscope analysis, which showed that emulsions with Span 20 had more consistent, smaller droplet sizes at 9.44 µm and 10.00 µm, respectively, which added to their stability. On the other hand, emulsions stabilised with Span 80 exhibited decreased stability as indicated by bigger droplet sizes and greater creaming indices. In addition to providing essential information for long-lasting VCO-based emulsions for various industrial applications, the study emphasises the relevance of selecting the appropriate surfactants to improve the stability of emulsions. These discoveries enhance the progress of creating more enduring emulsions based on virgin coconut oil, which may be used in a wide range of applications such as cosmetics, food and drug deliveries.